Hubungan Kesadaran Metakognitif Peserta Didik Dengan Hasil Belajar Biologi - Ai Anisa Asaidah; Romy Faisal Mustofa; Diki Muhamad Chaidir (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
This study aims to determine the correlation of metacognitive awareness with biology learning outcomes of students in class XI IPA MA Negeri 1 Tasikmalaya City which was conducted in May 2021. This research is a correlational study. The population in this study were all students of class XI IPA MA Negeri 1 Tasikmalaya City as many as 4 classes. The sample selection in this study used a purposive sampling technique as many as 67 students of class XI IPA 3 and class XI IPA 4. The data collection techniques used in this study were questionnaires and interviews. The results of data analysis showed that there was a relationship between metacognitive awareness and biology learning outcomes with a correlation coefficient value of 0.531 meaning that it had a moderate correlation, and a significance value of 0.000 <0.05 was obtained. The conclusion of this study is that there is a relationship between metacognitive awareness and learning outcomes of biology class XI IPA MAN 1 Tasikmalaya City.